Green taxes, R&D investments, and emission abatement - Di Yin; Chang Youngho (Asian Development Bank Institute (ADBI), 2020)
This study explores how energy tax influences energy R&D investments, which further affect economic welfare, carbon emissions, and climate change under various emission abatement policies. Energy tax, as a market-based instrument, aims to adjust the energy R&D investments to the optimal level. The study considers two types of energy tax, the optimal energy tax and the Pigovian tax. The optimal energy tax contains the scarcity rent and the carbon tax, while the Pigovian tax only considers the carbon tax. Setting the energy tax equal to the Pigovian tax appears to be insufficient, leading to sub-optimal outcomes. The impact is more significant before the energy use transits from fossil fuels to backstop technology, while the impact is moderate after the backstop technology fully replaces fossil fuels. The study shows that the sub-optimal outcomes are worse with a more restrictive abatement policy, while they are moderate under a less stringent abatement policy.
Keywords: Q52; Q55; Q58; 330; optimal energy tax; Pigovian tax; scarcity rent; carbon tax; energy substitution; backstop technology; benefit-cost analysis